The effect of pore size on cell behavior in mesoporous bioglass scaffolds for bone regeneration. (December 2022) - Xia, Demeng; Wang, Yang; Wu, Rui; Zheng, Qingyuan; Zhang, Guoqiang; Xu, Shuogui; Zhou, Panyu
Highlights: MSX-3, MSX-8 MSX-20 have good biocompatibility and in vitro mineralization activity. MSX-20 had obvious adsorption/deposition effect on organic compounds like proteins. MSX-20 is more conducive to promote bone regeneration. MSX-20 promotes the adhesion of stem cells and sustained release of BMP-2. Abstract: The material properties of bone tissue repair scaffolds dictate the interaction between the material and tissues or cells in vivo . The interface between them at the nanoscale can regulate cell adhesion, migration, and differentiation behaviors, thereby reshaping osteogenic properties of the material in vivo . In this study, a series of 3 nm, 8 nm and 20 nm mesoporous bioactive glass scaffolds (MSX-3, MSX-8 and MSX-20) were prepared by employing sol-gel technique and active self-assembly, with mesoporous bioglass serving as matrix. We then further examined effects of different mesopore pore sizes on the material biology of scaffolds and effects of osteogenic properties both in vitro and in vivo . The prepared multi-level micro-nano-structured bone repair scaffolds all had ∼300 μm macropores and possessed good biocompatibility and in vitro mineralizing activity. In vitro mineralization experiments proved that a large amount of calcium and phosphate salts were deposited on the surfaces of MSX-3 and MSX-8 scaffolds, while MSX-20 had conspicuous adsorption/deposition effects on organic compounds such as proteins in solution. MSX-20 multi-level micro-nano-structured bone repair scaffold could significantly promote the cell adhesion of BMSCs, and the cell spreading area was significantly larger than that of MSX-3 and MSX-8 scaffolds. MSX-20 multi-level micro-nano structured bone repair scaffold had a good sustained release effect on BMP-2, which could promote the osteogenic differentiation effect of BMP-2 on BMSCs. In vivo animal experiments also showed that MSX-20 loaded with BMP-2 could significantly promote in vivo osteogenesis. These findings suggest that when the mesopore pore size is 20 nm, the scaffold can be more conductive to bone regeneration due to the enhanced adhesion of stem cells and more sustained release of BMP-2. Graphical abstract: Image, graphical abstract